Altered model-based prediction error signaling in the lateral orbitofrontal cortex in patients with obsessive-compulsive disorder: An fMRI study - Pritha Sen; Kathrin Koch; Benita Schmitz-Koep; Deniz Gürsel; Franziska Knolle (NeuroImage)
Background: Compared to healthy individuals, patients with obsessive-compulsive disorder (OCD) are found to rely more on model-free decision-making strategies which may underlie symptom expression. It is, however, unclear whether these behavioral differences are represented in neural alterations of model-free and model-based decision-making when tested simultaneously. Methods: We investigated the neural signatures of 22 OCD patients and 22 matched controls who completed a two-step Markov decision-making task during functional MRI scanning. We used hierarchical Bayesian modelling and Bayesian statistics to examine model-based and model-free decision-making behaviors. Parametric regressors were employed for model-free and model-based reward prediction errors to inform neural reward presentation, which we analyzed using a Bayesian Multilevel Modeling (BML) approach. Associations between significant activations and symptoms as well as cognitive scores were explored using Bayesian linear regression. Results: While controls received significantly more rewards and were significantly less stochastic compared to patients, both groups similarly relied on model-free decision-making strategies. Importantly, our group comparison of neural reward prediction error responses showed greater activation for model-based reward prediction error in the lateral orbitofrontal cortex (lateral OFC) in OCD patients compared to controls, but no differences for model-free reward prediction error processing. Increased lateral OFC activity was associated with lower obsessive symptoms and better cognitive functioning. Conclusion: These findings support the notion that OCD is associated with an altered goal-directed system, which may be expressed through increased activation in the lateral OFC activity underlying goal-directed behavior. Importantly, the hyperactivity observed in this region was linked to reduced obsessive symptoms and improved cognitive functioning, potentially indicating compensatory mechanisms and highlighting the lateral OFC as a potential target for future interventions.